A lab-scale study on the influence of the compost-dewatering process on moisture removal and pathogen inactivation in pre-sanitized fecal sludge. (3rd March 2022) - Odey, Emmanuel Alepu; Odey, John Adinya; Li, Zifu; Zhou, Xiaoqin
Abstract: In many developing cities, fecal sludge management has become a serious environmental issue. As the increasing urban settlement results in the generation of fecal matter that causes environmental problems, recovering and recycling fecal waste for soil amendment could be beneficial. In this study, pre-sanitized fecal sludge (FS) was collected from the ongoing FS treatment process at the University of Science and Technology Beijing and subjected to a compost-dewatering process to mitigate pathogen and moisture content (MC). Biochar and dry leaves were added to reactors 1, 2, and 3 (1:1, 2:1, and 3:1) at 10% to facilitate the degradation process. The result shows that the final MC from the 45-day experiment has values of 35.1, 37.3, 38.9, and 65% in reactors 1, 2, 3, and the control, respectively. The indicator organism (fecal coliform) was completely mitigated in reactors 1 and 2. However, fecal coliform was merely reduced from 7.2 to 5.7 log10 CFU/100 mL in reactor 3 and remained available in the control reactor. This phenomenon of pathogen inactivation and MC removal from FS was attributed to the concentration of lactic acid bacteria (LAB) in the pre-sanitized FS. The addition of LAB to the treatment process enhanced the acidification process and resulted in pathogen inactivation. Biochar and dry leaves also played an important role in mitigating moisture and enhancing the fast composting process. Given the hygienic condition of the compost, it is suitable for soil amendment in agriculture. HIGHLIGHTS: Composting process enhanced pathogen and odor removal from pre-sanitized fecal sludge (FS). Acidification of FS as a pre-treatment method serves as a reliable method for fecal hygienization. Short-term composting process proved effective in odor emission mitigation. Method employed in this research enhanced fecal coliform inactivation. Compost derived from the process has a high potential to be used as an agricultural resource. Graphical Abstract